PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, KOMPENSASI DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA KANTOR KESYAHBANDARAN DAN OTORITAS PELABUHAN PANTOLOAN - Agus, Muh. (Katalogis, 2017)
The objective of this study is to determine the influence of transformational leadership style, compensation and motivation on the  performance of officials in the maritime and port authority office of pantoloan.this study uses explanatory approach in explaining the relationship between variables by involving 70 officials in the maritim and port authority office as respondents, who were selected through census method. The result of the tests shows that: 1) transformational leadership, compensation and motivation simultaneously have  significant influence on on the officials ‘performance; 2) transformational leadership style is partially has positive and  significant influence  on the officials‘performance; 3) compensation partially has positive and significant influencet on the officials‘performance; 4) motivation partially has positive and significant influence on the office ‘performance.